14 Impact of epilepsy or seizures on outcomes following takotsubo cardiomyopathy. (6th June 2022) - Ahmed, Raheel; Sawatari, Hiroyuki; Irfan Wafa, Syed Emir; Padmanabhan, Deepak; Deshpande, Saurabh; Khanji, Mohammed; Somers, Virend; Chahal, Anwar
Abstract : Introduction: Takotsubo cardiomyopathy (TC) is often preceded by emotional or physical stress. Literature is conflicted on the effect of epilepsy or seizures on TC. We sought to test the association of epilepsy on readmission outcomes in patients with TC. Methods: Patients with TC during 2010–2015 were identified using International Classification of Diseases-9th Revision-Clinical Modification (ICD-9-CM) from the Nationwide Readmissions Database (NRD). Patient demographics, presence of comorbidities, time from discharge to readmission and the reason of readmission were also abstracted from the database. Patients with TC were divided into those with a prior history of epilepsy or seizures vs those without. Results: From 2010 to 2015, 32, 817 TC patients were included in the analysis out of which epilepsy or seizure were present in 1, 698 (5.17%) patients. At baseline first admission, patients with epilepsy or seizure, vs. those without, were younger [61.0 (53.0–71.0) vs 68.0 (59.0–78.0), p<0.0001], less likely to be females [82.6% vs 87.5%, p<0.0001], had greater length of stay (LOS) [5.0 (3.0–11.0) vs 3.0 (2.0–7.0), p<0.0001], greater adjusted healthcare associated costs (HAC) [median [IQR]: US15, 959.6 (9, 401.8–32, 371.7) vs 11, 193.7 (7, 432.6–19, 414.6), p< 0.0001], similar Charlson comorbidity index [2.0 (1.0–3.0) vs 2.0 (1.0–3.0), p=0.06], less likely to have atrial fibrillation [10.5% vs 16.0%, p<0.0001] but more likely to have ventricular fibrillation [2.3% vs 1.0%, p<0.0001] or cardiac arrest [5.1% vs 2.0%, p<0.0001]. On readmission, patients with epilepsy or seizure had similar in-hospital mortality (3.3% vs 4.0%, p=0.47), LOS (median [IQR]: 4 [2–7] vs 4 [2–7] days, p=0.83) and adjusted HAC (median [IQR]: US8151.4 [5041.4–15000.3] vs 8143.1 [4838.8–15551.5], p=0.80). However, freedom from all-cause readmission was higher in patients without epilepsy or seizure at 90-days follow-up (HR[95%CI]: 1.32 (1.19–1.46), p<0.0001). Conclusions: Presence of epilepsy or seizure was associated with a higher frequency of VF, cardiac arrest, increased length of stay and adjusted HCAC on index admission with TC. Background history of epilepsy or seizure also increases all-cause readmissions at 90-days in patients with initial presentation of TC. However, there is no significant difference in length of stay, healthcare adjusted costs and mortality on readmission. Further assessment to determine the causes of readmissions may help to identify preventable factors during index admission. Conflict of Interest: None